2001
DOI: 10.1103/physreve.63.041602
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo studies of model Langmuir monolayers

Abstract: This paper examines some of the basic properties of a model Langmuir monolayer, consisting of surfactant molecules deposited onto a water subphase. The surfactants are modeled as rigid rods composed of a head and tail segment of diameters sigma(hh) and sigma(tt), respectively. The tails consist of n(t) approximately 4-7 effective monomers representing methylene groups. These rigid rods interact via site-site Lennard-Jones potentials with different interaction parameters for the tail-tail, head-tail, and head-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…But, one of the difficulties for such simulations is the adequate definition of effective interactions between the Bgrains.脦 nvestigations of the surfactant behavior at different interfaces using the Monte Carlo method are not so numerous. Nevertheless, corresponding studies enable the estimation of the structural features for surfactant films [132,133], chiral effects in monolayers [134], impact of the structural peculiarities of the surfactants on the parameters of the phase transitions in the monolayers [135]. In the framework of the continuum configurational bias Monte Carlo method Howes and Radke [132] got surface tension isotherms of nonionic amphiphiles and calculated the tilt angles of the surfactant molecules with respect to the interface.…”
Section: Molecular Mechanicsmentioning
confidence: 99%
See 1 more Smart Citation
“…But, one of the difficulties for such simulations is the adequate definition of effective interactions between the Bgrains.脦 nvestigations of the surfactant behavior at different interfaces using the Monte Carlo method are not so numerous. Nevertheless, corresponding studies enable the estimation of the structural features for surfactant films [132,133], chiral effects in monolayers [134], impact of the structural peculiarities of the surfactants on the parameters of the phase transitions in the monolayers [135]. In the framework of the continuum configurational bias Monte Carlo method Howes and Radke [132] got surface tension isotherms of nonionic amphiphiles and calculated the tilt angles of the surfactant molecules with respect to the interface.…”
Section: Molecular Mechanicsmentioning
confidence: 99%
“…Selinger and Selinger [134] applied the continuum elastic theory together with 袦小 simulations for the prediction of defects in the monolayer resulting in macroscopic chiral symmetry. Investigations of the influence of the diameter of the surfactant hydrophilic and hydrophobic parts done by Opps et al [135] showed that an increasing mismatch of these diameters results in the decrease of the critical temperature for the transition between inclined and upright phases.…”
Section: Molecular Mechanicsmentioning
confidence: 99%
“…Bead spring models without explicit solvent have also been used to simulate bilayers [40,145,146] and Langmuir monolayers [148,149,150,151,152]. The amphiphiles are then forced into sheets by tethering the head groups to two dimensional surfaces, either via a harmonic potential, or via a rigid constraint.…”
Section: Iiib Chain Models In Continuous Spacementioning
confidence: 99%
“…Therefore, Haas et al [148,149] represent the amphiphiles as stiff LennardJones chains, with one end (the head bead) confined to move in a plane. In later versions of the model [150,151,152], the head bead interactions differ from those of the tail beads: They are taken to be purely repulsive, and the head size is variable. which is distorted in the direction of tilt.…”
Section: Iiib Chain Models In Continuous Spacementioning
confidence: 99%
“…These isotherms show a number of distinct regions that correspond to the two dimensional analogs of the monolayer usual states. [2][3][4] Various studies have reported isotherms where a number of states and the equilibrium between them have been clearly identified as the monolayer is compressed. [4][5][6] When the area per molecule is very large, the monolayer is in a vapor phase 蛻V蛼.…”
Section: Introductionmentioning
confidence: 99%